Profil radiographique et tomodensitométrique des métastases vertébrales : cas du CHU Sylvanus OLYMPIO (CHU SO) de Lomé (TOGO) - DIALLO Mamadou Lamarana; WATARA Gani; BALDE Alpha Abdoulaye; GBANDE Pihou; KEITA Abdoulaye Kobele; ONIANKITAN Owonayo; AGODA-KOUSSEMA Lama Augustin Kegdigoma (Journal Africain d Imagerie Médicale (J Afr Imag Méd) Journal Officiel de la Société de Radiologie d’Afrique Noire Francophone (SRANF), 2025)
Objective : to describe the profile of vertebral bone metastases on standard X-ray and CT scan. Method : descriptive cross-sectional study with retrospective data collection, covering a period of 05 years (January 1st 2017 to December 31st 2022). It focused on the files of patients hospitalized in the Rheumatology department of the S.O. University Hospital of Lomé for vertebral metastases revealed by a standard X-ray and/or a CT scan. The variables studied were quantitative (frequency, age) and qualitative (sex, primary cancer, imaging modalities, spinal level affected, sites of lesions, radiographic and CT semiology). Results: In total, 35 cases were selected out of 776, i.e. a frequency of 4.5%. The mean age of the patients was 59.5 +/- 10.2 years with extremes of 27 and 86 years. The 61-70 age group was the most represented (28.5%). The male predominance remains classic (62.9%) with a sex ratio of 1.7. Prostate cancer was the main primary of these lesions (54.3%). Vertically, involvement of the thoraco-lumbosacral levels was the most common (48.5%). Horizontally, the involvement was preferentially corporeal (80% at the lumbosacral level and 68.5% at the thoracic level). Diffuse homogeneous condensations (34.2%) were the most common lesions. LODWICK Ic gaps (25.6%) were most often accompanied by posterior cortical lysis (8.5%) and epiduritis (17.1%). The mixed lesions associated LODWICK type II deficiencies with heterogeneous condensation. Pedicle cortical lysis, a telltale sign in standard radiography, was unilateral (20%) and bilateral (22.9%). Conclusion: Standard radiographs and CT scans are sometimes sufficient for the diagnosis of vertebral metastases despite the risk of late diagnosis.